War as a Redistributive Problem. Issue 1 (8th June 2021) - Davis, Jason Sanwalka
Abstract: War is commonly conceived of as the result of a bargaining process between states. However, war also has redistributive consequences within a state: certain groups face disproportionate costs (e.g., likely conscripts), whereas other groups may accrue most of the benefits (military contractors, politicians, etc.). War should thus be viewed simultaneously as the result of a bargaining process between domestic groups. This article presents a two‐level game in which the relative importance of domestic groups to a government can impact the likelihood of going to war, but only under certain conditions. In particular, a necessary condition for domestic distributive politics to matter for war onset is the existence of redistributive frictions between domestic parties. This allows the model to produce a new explanation for why war may occur despite the fact that it is Pareto inefficient: inability to costlessly redistribute value between war's beneficiaries and the beneficiaries of any peaceful bargain.